Die Windverhältnisse im Rhein-Main-Gebiet, eine Studie zur dynamischen Klimatologie der Mittelgebirge - Dammann, Walter (ERDKUNDE, 1960)
The object of the paper is an analysis of the data of wind statistics from sypnotic-climatological aspects. On the basis of observation material for the three years 1936-1938, for which period there are also available the data of weather flights, allowing the establishment of the thermic stratification of the atmosphere, it was possible to show that under certain atmospheric conditions there originates nightly an independent minor wind system with a vertical axis and air flow convergence along the Rhine Rift Valley. The mountain and valley wind systems of the Odenwald and Haardt Hills are incorporated in it. The meteorological basis of this wind systems is a pronounced temperature inversion (during south-east weather) with an upper limit lying higher than the altitude of the bordering mountains, thus screening the air body of those altitudes against the higher parts of the atmosphere. It appears that in addition to the thermic conditions, dynamic effects, caused by the forced deflection of the air masses flowing across the bordering mountains in conditions of stable stratification and nearly laminar flow contribute also. It is suggested that under those conditions in the lee of the Odenwald above the Rhine valley there is possibly a tendency to a weak trough of low pressure, as it is known to occur in a much more pronounced way on the lee sides of the high mountain ranges of the earth when they are crossed by air currents. It is, however, characteristic of the way the atmosphere works that this dynamic effect becomes inoperative as soon as the inversion has been destroyed by sufficient temperature increase after sunrise, and the air flow has changed its character by a vertical exchange of the air bodies. Similarly this subordinate wind system does not even commence during weather conditions a priori characterised by unstable air stratification, like cyclonic west weather, although under these conditions air currents across the Rhine Rift Valley also occur. In those cases the wind direction in the valley is similar to that higher up, and the effect of mechanical deflection by the edges of the bordering mountains is slight and noticeable only during the night. No independent wind system originates as in the former case. These differences due to weather conditions are substantiated by the appended tables and maps. The result throws light on a process within the windfield of the German Uplands, so far almost ignored, which, though less important geographically in comparison with the blocking or foehn effect, may nevertheless assume considerable importance for the air changes and the aerosol of the Rhine-Main basin with increasing industrialisation. It could be demonstrated by means of synoptic-climatological methods used by the author several times in previous papers.